2016
DOI: 10.1016/j.radonc.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Real-time in vivo dosimetry in high dose rate prostate brachytherapy

Abstract: Material and methods IVD was performed for 40 treatments planned using intra-operative trans-rectal ultrasound (TRUS) with a MOSFET inserted into an additional needle. Post-treatment TRUS images were acquired for 20 patients to assess needle movement. Monte Carlo simulations of treatment plans were performed for 10 patients to assess impact of heterogeneities.Per-needle and total plan uncertainties were estimated and retrospectively applied to the measured data as error detection thresholds. ResultsThe mean me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 22 publications
(28 reference statements)
3
18
1
Order By: Relevance
“…Interestingly, the distance dependence appeared to be due to the response of the detector, given the consistency of absorbed dose estimations by Monte Carlo methods, by the planning system, and by the radiochromic film measurements, whereas the detector response varied, which can be attributed to the energy dependence of the detector. Mason et al measured the relative response normalized to a distance of 1.5 cm from the detector and showed a linear fit with R 2 value of 0.457 vs. our finding of 0.785, with a slope value of 0.026 cm −1 vs. our result of (0.014 ± 0.001) cm −1 . Mason et al described a value of 0.975 for the ordinate origin, highly similar to the value of 0.975 in our study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Interestingly, the distance dependence appeared to be due to the response of the detector, given the consistency of absorbed dose estimations by Monte Carlo methods, by the planning system, and by the radiochromic film measurements, whereas the detector response varied, which can be attributed to the energy dependence of the detector. Mason et al measured the relative response normalized to a distance of 1.5 cm from the detector and showed a linear fit with R 2 value of 0.457 vs. our finding of 0.785, with a slope value of 0.026 cm −1 vs. our result of (0.014 ± 0.001) cm −1 . Mason et al described a value of 0.975 for the ordinate origin, highly similar to the value of 0.975 in our study.…”
Section: Discussionsupporting
confidence: 78%
“…In relation to the response dependence on the source‐detector distance, we found a variation of (5.76 ± 0.03)% (k = 1) between distances of 1 and 5 cm, lower than the variation of 10.4% reported by Mason et al for these distances, which led them to propose a correction of 2.6% cm −1 in the detector reading. Interestingly, the distance dependence appeared to be due to the response of the detector, given the consistency of absorbed dose estimations by Monte Carlo methods, by the planning system, and by the radiochromic film measurements, whereas the detector response varied, which can be attributed to the energy dependence of the detector.…”
Section: Discussioncontrasting
confidence: 77%
“…For this setup, the standard error of the mean is equal to 50% of the standard deviation. This dose difference is in the range of published uncertainties for in vivo dosimetry in HDR brachytherapy (Mason et al 2016;Belley et al 2018). Finally, all ten fractions of the clinical HDR plan were consecutively delivered, amounting to a dose of at least 300 Gy to the surface of the applicator, and the applicator was monitored for structural damage.…”
Section: Testing and Validationmentioning
confidence: 99%
“…Deviations were often attributed to detector positioning uncertainties that depend on the experience of the user, verification methods, proper fixation and possible anatomical changes during the treatment. Catheter and needle reconstruction were also identified as a potential source of clinically relevant deviations [56]. One study reported that improvements in the workflow and imaging immediately prior to treatment delivery reduced maximum dose deviation from 67% to 9% [54]; indeed, deviations between measured and planned dose generally increase as the time between imaging and treatment delivery increases [47].…”
Section: Clinical Studiesmentioning
confidence: 99%